Juvenile dermatomyositis complications: navigating gastrointestinal perforations and treatment challenges, a case report - Xiangyuan, Chen; Xiaoling, Zeng; Guangchao, Sun; Huasong, Zeng; Dexin, Liu (Frontiers in Pediatrics, 2024)
Juvenile dermatomyositis (JDM) is a rare autoimmune disorder with multi-system involvement, often presenting with a heliotrope rash, Gottron's papules, and proximal muscle weakness. JDM patients with anti-nuclear matrix protein 2 (anti-NXP2) positivity tend to have more severe manifestations, including a higher risk of gastrointestinal (GI) complications such as dysphagia, intestinal motility changes, edema, malabsorption, ulcers, and perforations. These complications are associated with poor outcomes and high mortality rates, particularly in patients with anti-NXP2 positivity. A case is presented of a 12-year-old girl with JDM who developed multiple GI perforations after being treated with high-dose methylprednisolone. Despite multiple surgical attempts, the patient experienced continued leakage and new perforations. The treatment approach was shifted to include jejunostomy, plasma exchanges, fresh frozen plasma support, and tofacitinib, leading to gradual improvement in muscle strength and reduction in inflammation. GI involvement in JDM is a significant concern due to its association with poor prognosis and high mortality. The use of high-dose glucocorticoids must be carefully considered in JDM patients with GI involvement, as they may contribute to the development of perforations and complicate treatment. A combination of plasma exchange, fresh frozen plasma support, low-dose glucocorticoids, and Janus kinase inhibitors may offer a safer treatment strategy for managing refractory JDM with GI complications. The case highlights the importance of a multidisciplinary approach to treatment and the need for further research to determine the necessity of high -dose glucocorticoid therapy following GI involvement in JDM.